An Interfacial Layer Based on Polymers of Intrinsic Microporosity to Suppress Dendrite Growth on Li Metal Anodes. Issue 52 (27th August 2019) - Qi, Liya; Shang, Luoran; Wu, Kai; Qu, Liangliang; Pei, Hao; Li, Wen; Zhang, Lexiang; Wu, Zhengwei; Zhou, Henghui; McKeown, Neil B.; Zhang, Weixia; Yang, Zhengjin
Abstract: The performance and safety of lithium (Li) metal batteries can be compromised owing to the formation of Li dendrites. Here, the use of a polymer of intrinsic microporosity (PIM) is reported as a feasible and robust interfacial layer that inhibits dendrite growth. The PIM demonstrates excellent film‐forming ability, electrochemical stability, strong adhesion to a copper metal electrode, and outstanding mechanical flexibility so that it relieves the stress of structural changes produced by reversible lithiation. Importantly, the porous structure of the PIM, which guides Li flux to obtain uniform deposition, and its strong mechanical strength combine to suppress dendrite growth. Hence, the electrochemical performance of the anode is significantly enhanced, promising excellent performance and extended cycle lifetime for Li metal batteries. Abstract : A thin, robust and flexible interfacial layer with 3D interconnected pores that is based on a polymer of intrinsic microporosity (PIM) has been prepared using a simple spin‐coating method. The PIM film has a unique porous structure and strong mechanical strength, which can sufficiently suppress the dendrite growth on Li metal anodes, resulting in a high coulombic efficiency (≈98.3 %) and a long cycle life of over 200 cycles (see figure).